2020
DOI: 10.1074/mcp.ra119.001797
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic Characterization of the Mode of Action of a Potent New Antimalarial Compound, JPC-3210, Against Plasmodium falciparum

Abstract: The increasing incidence of antimalarial drug resistance to the first-line artemisinin combination therapies underpins an urgent need for new antimalarial drugs, ideally with a novel mode of action. The recently developed 2-aminomethylphenol, JPC-3210, (MMV 892646) is an erythrocytic schizonticide with potent in vitro antimalarial activity against multidrug-resistant Plasmodium falciparum lines, low cytotoxicity, potent in vivo efficacy against murine malaria, and favorable preclinical pharmacokinetics includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 58 publications
5
46
0
Order By: Relevance
“…The alternative hypothesis that these secondary pathways are non-specific responses in dying parasites is also possible. However, different drug-specific biochemical responses were reported in metabolomics, proteomics and peptidomics studies of other antimalarials, including the 4-aminoquinolines that target the digestive vacuole via a different mechanism, and even when parasites were exposed to drugs for extended durations [ 45 47 , 79 , 80 ]. Combined with reports showing that peroxide antimalarials target proteins in both the phospholipid and pyrimidine biosynthesis pathways [ 19 , 20 , 27 ] and colocalise with neutral lipids within iRBCs [ 70 , 71 ], the drug-specific biochemical responses of parasites detected in metabolomics studies suggests that the secondary metabolic alterations observed here are likely ozonide-specific and related to the pleiotropic effect of peroxides on parasite metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The alternative hypothesis that these secondary pathways are non-specific responses in dying parasites is also possible. However, different drug-specific biochemical responses were reported in metabolomics, proteomics and peptidomics studies of other antimalarials, including the 4-aminoquinolines that target the digestive vacuole via a different mechanism, and even when parasites were exposed to drugs for extended durations [ 45 47 , 79 , 80 ]. Combined with reports showing that peroxide antimalarials target proteins in both the phospholipid and pyrimidine biosynthesis pathways [ 19 , 20 , 27 ] and colocalise with neutral lipids within iRBCs [ 70 , 71 ], the drug-specific biochemical responses of parasites detected in metabolomics studies suggests that the secondary metabolic alterations observed here are likely ozonide-specific and related to the pleiotropic effect of peroxides on parasite metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The Hb fractionation assay was adapted from [ 35 , 80 ]. Briefly, 3D7 trophozoite-stage parasites were incubated with DHA, OZ277, OZ439, E64d or a DMSO control for either 1 or 3 h. Following incubation, Hb, haem and haemozoin species were separated and measured using the Hb fractionation assay [ 35 , 80 ], and smears were made using Giemsa stain to check for parasite viability and digestive vacuole morphology by light microscopy. For the Hb fractionation assay, the samples were normalised via a paired analysis to the DMSO control and graphed as their fold change vs DMSO ± SD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics LC-MS/MS data was acquired using Dionex Ultimate® 3000 RSLCnano system coupled to Q Exactive HF mass spectrometer (Thermo Scientific) carried out as described previously 78 , with minor modifications. MS2 data was collected in data independent mode (DIA) with a 33-fixed window setup of 18 m/z effective precursor isolation over the m/z range of 375-975 Da.…”
Section: Liquid Chromatography Mass Spectrometry (Lc-ms/ms) Analysismentioning
confidence: 99%
“…Raw files were processed using Spectronaut TM 13.0 against an in-house generated asexual P. falciparum spectral library. The library contained 44 449 peptides corresponding to 4730 proteins, of which 3113 were P. falciparum proteins 78 . For processing, raw files were loaded and Spectronaut calculated the ideal mass tolerances for data extraction and scoring based on extensive mass calibration using a correction factor of one.…”
Section: Chemical Proteomics Data Analysismentioning
confidence: 99%